The Effect of Service Quality, Price, and Product Variety on Consumer Buying Interest in UD Building Stores. Namira - Windiyatin Zulia Ningse; Imam Syairozi; Abid Muhtarom (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the influence of product innovation, product quality, and service quality on customer satisfaction in the Risqi Tailor Sewing Business. The study uses a quantitative approach with a population of 730 Risqi Tailor customers in 2023. The number of samples was determined using the Slovin formula with an error rate of 10%, so that 87 respondents were obtained. Data were collected through a Likert scale questionnaire and analyzed using SPSS version 25 through validity, reliability, classical assumptions, multiple linear regression, multiple correlation, determination coefficient, t-test, and F-test. Product quality had a positive and significant effect with a t-value of 9.952 and a significance of 0.000. The quality of service also had a positive and significant effect with a t-value of 2.432 and a significance of 0.017. Simultaneously, product innovation, product quality, and service quality had a significant effect on customer satisfaction with an F value of 107.225 and a significance of 0.000. Square's R-value of 0.795 indicates that 79.5% of the variation in customer satisfaction is explained by all three study variables, while the remaining 20.5% is explained by factors other than the model. The most dominant variable is product quality.